Preparation and Characterization of Liquid Fertilizers Produced by Anaerobic Fermentation - Juan Francisco López-Rubio; Cristina Cebrián-Tarancón; Gonzalo L. Alonso; Maria Rosario Salinas; Rosario Sánchez-Gómez (Agriculture)
Biol is a liquid product, obtained by anaerobic fermentation of local inputs, which improves the health of agroecosystems, which is an emerging area in agronomy. The aim of this study consists of the preparation of two biols from inoculums of cow dung (BCD) and native forest duff (BNF) by using specific biodigesters and commercial inputs. The biol characterization was made in terms of mineral (ionic and complex forms), amino acids, hormones and volatile compounds, along with Pfeiffer circular chromatography during fermentation monitoring. The results showed a pH acidic in both biols (4.5–5.5), which is higher for BCD. Also, this biol had higher content in several macro- and micronutrients in ionic (nitrates, phosphates, calcium, iron and sodium) and complex forms (calcium, iron and potassium). Both have interesting content in amino acids and hormones. The absence of microorganisms in the final products could be due to the presence of volatile compounds such as pyrazines and sulfoxides. Along with this, other volatile compounds such as esters were identified, which can be responsible for their pleasant odor. The novelty of this work is to provide a protocol for obtaining biols and to demonstrate their potential to be used as biofertilizers.